Pengembangan Training Kit Multi Sensor Terintegrasi Smart Relay Zelio SR2B201FU Untuk Meningkatkan Kreativitas Teknis Mahasiswa - Nanda Julian AlFaris; Fendi Achmad; Yulia Fransisca; Ali Nur Fathoni (Educational Journal, 2026)
This study aims to develop a multi-sensor training kit integrated with the Smart Relay Zelio SR2B201FU. The primary objective of this development is to enhance students' technical creativity in dealing with complex intelligent control systems. Through this training kit, students are expected to have a practical platform to explore the integration of various types of sensors into industrial automation systems. The research method employed is Research and Development (R&D). The development process includes the hardware design phase, the preparation of accompanying jobsheets, and supporting instruments such as response questionnaires and observation sheets. Product feasibility was tested through media and material expert validation, while practicality and effectiveness were tested directly on students by comparing learning outcomes before and after using the kit. The results indicate that the training kit is highly feasible, with media expert validation scoring 78% and jobsheet material scoring 76%. The practicality score from students reached 84% (Very Practical). In terms of effectiveness, statistical tests showed a significant difference with a value of 0.000 and an average N-gain of 0.55 (moderate category). These findings prove that the integration of motion, light, sound, and mechanical sensors in this learning media successfully enhances students' ability to explore technical solutions creatively.